Clean and efficient recovery of spent LiCoO2cathode material: Water-leaching characteristics and low-temperature ammonium sulfate calcination mechanisms. (20th September 2020) - He, Shichao; Wilson, Benjamin P.; Lundström, Mari; Liu, Zhihong
Abstract: LiCoO2 lithium-ion batteries are disposed once their life cycle comes to an end, by which large amounts of extremely harmful heavy metals and organic compounds are released into the environment. Further, the spent LiCoO2 cathode material from spent lithium-ion batteries contains numerous high-grade metals with a high recovery value, such as Li, Co and Mn. Hence, a clean and efficient process is proposed in this research for recovery of spent LiCoO2 cathode material via low-temperature (NH4 )2 SO4 calcination and water-leaching.The calcination temperature range between 445.87 and 677.48 °C is determined from analysis of the TG-DTA curve obtained with n (2Li + Co + Mn): n (NH4 )2 SO4 of molar ratio = 1:1. The sample calcined under conditions of calcination temperature of 600 °C, calcination time of 45 min and an (NH4 )2 SO4 excess of 1.2 exhibits optimal water-leaching efficiencies of the Li, Co and Mn elements, which are 99.50%, 98.53%, and 94.41%, respectively. Reaction mechanisms of the low-temperature calcination process are investigated with both SEM and XRD analyses of the differently prepared samples and their residues following water-leaching. Results show that the calcination of spent LiCoO2 cathode material with (NH4 )2 SO4 is a liquid-solid reaction with the spent cathode material particles being gradually eroded and consumed from the outer layer. In addition, the presence of free high-energy H + released by the decomposition of NH4 + generated by molten (NH4 )2 SO4 plays a leading role in the whole calcination process, the structure of LiCoO2 and LiMn2 O4 are broken down before eventually being converted into soluble sulfate salts. Graphical abstract: Image 1 Highlights: A clean-efficient process is proposed for recovery of spent LiCoO2 cathode material. The water-leaching characteristics of calcinated samples are investigated in detail. 99.50% Li, 98.53% Co, 94.41% Mn present in the spent cathode material are recovered. The mechanisms of spent cathode material calcinated with (NH4 )2 SO4 are investigated.